Multimedia Communications / Applications, Networks, Protocols and Standards - Halsall Fred (Addison-Wesley Publishing Company, 2001)
An essential reference for computing and networking professionals. Preface, Acknowledgements, Multimedia Communications, Multimedia Information Representation, Text and Image Compression, Audio and Video Compression, Standards for Multimedia Communications, Digital Communication Basics, Circuit-Switched Networks, Enterprise Networks, The Internet, Broadband ATM Networks, Entertainment Networks and High-Speed Modems, Transport Protocols, Application Support Functions, Internet Applications, The World Wide Web, Bibliography, Index.